Ingessana Goats Phenotype, Carcass and Wholesale Cuts Characteristics in Fadamia, Bao Locality, Blue Nile State, Sudan - Elimam, Mohmed E; Hamed, Asma H.M; Abdalla, Amer A. Y (Animal Review, 2015)
Two studies were conducted to characterize the phenotype, carcass and wholesale cuts in Ingessana goats in Fadamia, Bao Province, Blue Nile State, Sudan which is about 521km south east of Khartoum. In the first study 250 animals were used to study body weight and measurements and colours at different ages in villages in the area. In the second study 6 males at <1 and 1 year old (three in each age group) were used to study body components and carcass and wholesale characteristics. The data was statistically analyzed according to MSTAT. Body weight (BW) and measurements, except horns and tail length, were increased with age. The correlations between BW and measurements were calculated and different regression equations were used to predict BW from some body weight at different ages with no significant (P>0.05) differences between measured and predicted BW. Animals’ colours varied greatly and were mainly black and white (35%). All body components percentages, except skin and small intestines, were higher at <1 year old with no significant difference between the two age groups. Slaughter weight, empty BW (EBW) and hot carcass weight were significantly (P <0.05) higher at1 year old. Dressing percentages were higher on EBW than LBW and were not significantly (P>0.05) different between the two age groups. Carcass muscle, bone, fat and muscle: fat were not significantly (P>0.05) different between the two age groups. Muscle: fat was significantly higher at 1 year old (P<0.05). There were no significant (P>0.05) differences in all wholesale cuts percentages between the two age groups. The percentages of leg and chump, single short forequarter and loin were higher at 1 year old and breast and neck percentages were higher at <1 year old.